Storm Water Control Effect of Low Impact Development Facilities Based on SWMM: A Case Study of Yaohu Campus of Nanchang Institute of Technology - ZHANG Jingrong; LIU Weilin; WAN Yifan; LIU Jianwu; ZHONG Jinghao; LIU Lina (Renmin Zhujiang)
With the rapid development of urbanization, the problem of urban waterlogging is becoming increasingly serious. In order to solve the problem of urban waterlogging, the Yaohu Campus of Nanchang Institute of Technology was studied, and a storm water management model (SWMM) was constructed. In addition, low impact development (LID) facilities were added to analyze the control effect of LID facilities on rainfall runoff in the study area under different return periods of rainstorms before and after the construction of LID facilities, so as to provide a scientific basis and reference for the construction of a sponge campus. The results indicate that :①The storm water simulation results of SWMM in the study area are in good agreement with the actual situation after parameter adjustment, demonstrating good applicability; ② LID facilities have a good control effect on rainfall runoff; ③ The construction of LID facilities can better reduce the peak flow of the drainage outlet in the study area. With the reduction of the rainstorm return period, the reduction rate basically remains unchanged, and the delay effect on the peak moment of the drainage outlet is enhanced; ④ After the construction of LID facilities, the runoff at the peak moment of each subcatchment area in the study area is reduced by about 0.02 m3/s, and the runoff at the peak moment of areas with large runoff such as dormitories and libraries can be reduced to about 0.05 m3/s, reducing the impact of rainfall runoff on the travel of teachers and students.